The over-the-counter theory of the fed funds market: A primer - Gara Afonso; Ricardo Lagos (Federal Reserve Bank of New York, 2013)
We present a dynamic over-the-counter model of the fed funds market, and use it to study the determination of the fed funds rate, the volume of loans traded, and the intraday evolution of the distribution of reserve balances across banks. We also investigate the implications of changes in the market structure, as well as the effects of central bank policy instruments such as open market operations, the Discount Window lending rate, and the interest rate on bank reserves.
Keywords: G1; C78; D83; E44; 330; Fed funds market; search; bargaining; over-the-counter